2013
DOI: 10.1086/673146
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention of Physician Trainees and Medical Students to Practice Hand Hygiene

Abstract: Physician trainees were surveyed to assess intention to perform hand hygiene (HH). Compared with preclinical medical students (MS), clinical MS and residents reported less confidence that HH prevents carrying home microorganisms (P = .006, P = .003) or protects oneself from antibiotic-resistant microorganisms (P = .01, P = .006). Clinical trainees may need targeted interventions focusing on intention to perform HH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Hand washing is accepted as the most effective, economical, and the easiest infection control measure all over the world. 7,8 World Health Organization reported that 45% of gastrointestinal and 10 to 44% of respiratory tract infections could be prevented just by improved HHPs. 9 This study showed that HHPs of the mothers, main caregivers of the pediatric patients after the pediatric staff in pediatric wards, were mainly affected by age, education level, and the anxiety they experienced in the peroperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Hand washing is accepted as the most effective, economical, and the easiest infection control measure all over the world. 7,8 World Health Organization reported that 45% of gastrointestinal and 10 to 44% of respiratory tract infections could be prevented just by improved HHPs. 9 This study showed that HHPs of the mothers, main caregivers of the pediatric patients after the pediatric staff in pediatric wards, were mainly affected by age, education level, and the anxiety they experienced in the peroperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Another predictive factor in this model of IPC behaviour is perceived benefits. Previous research has shown that as medical students progress towards the final years of their training they are less likely to see the value of hand hygiene for protecting themselves from acquiring antibioticresistant microorganisms and to prevent carrying microorganisms home (Limper et al, 2013).…”
Section: Actionmentioning
confidence: 99%
“…Despite all the efforts made in the field of hand hygiene and the use of various methods to improve it, results of other studies suggest low levels of hand hygiene among health care students. 7 Compliance with hand hygiene varies based on hospital, department and working conditions. 8 Hand hygiene compliance is affected by several factors including the personal knowledge of hand hygiene, perception of the benefits, professional background, gender, infectious disease severity, work intensity and presence of facilities.…”
Section: Introductionmentioning
confidence: 99%